USING AUDIO MATERIALS TO IMPROVE STUDENTS' SPEAKING SKILL - Saidkazieva Diyora Atabekovna (Journal of new century innovations, 2023)
Abstract: This article highlights using audio materials to improve students’ speaking skills. Audio sources like podcasts, audiobooks, lectures, and even voice recording software, can significantly improve learners' listening and speaking skills, which can help them to communicate fluently and effectively in various contexts. However, optimal use of these audio materials requires certain strategies from the teachers, including appropriate selection of audio sources, providing listening and speaking support, and follow-up activities that reinforce learning. By adopting these strategies, teachers can help learners gain confidence, improve pronunciation, expand vocabulary, and develop fluency and interaction skills in the target language. Overall, the effective use of audio materials presents an innovative and practical approach to language instruction that can enhance learners' communicative competence.